Difficulties translating research on forensic interview practices to practitioners: Finding water, leading horses, but can we get them to drink? - Lamb, Michael E (The American psychologist, 2016)
Over the last 3 decades, researchers have elucidated the cognitive and motivational conditions that affect the capacity and willingness of young alleged victims to describe their experiences to forensic interviewers. Applied researchers have also studied the contents and features of training programs designed to help interviewers take advantage of the research on developmentally appropriate interviewing. The latter studies have highlighted a knowledge transfer problem-scientists understand best-practice techniques well, many interviewers believe that they both understand and employ those practices, but widespread training has had a limited impact on the actual quality of interviews conducted in the field. There is now clear evidence that improvements in interviewing practice occur reliably only when training courses involve multiple modules, distributed over time, with repeated opportunities for interviewers to consolidate learning and to obtain feedback on the quality of the interviews they do conduct. Barriers to the implementation of such training are discussed. (PsycINFO Database Record